Mut L Homolog 1 (Mlh1) Exon 16 Mutational Analysis in Ghanaian Colorectal Cancer Patients on Treatment at the Korle- Bu Teaching Hospital - Dorbu, A.S. (University of Ghana, 2023)
Background: Colorectal cancer (CRC), commonly known as cancer of the colon or rectum is a significant cause of morbidity and mortality around the world. In developing nations, notably in Sub-Saharan Africa, colorectal cancer is becoming more common. According to World Cancer Research Fund International Statistics in 2020, colorectal cancer is the third most common cancer worldwide. It is the third most common cancer in men and the second most common cancer in women with approximately 1.9 million new cases and 900,000 expected deaths. In Ghana's capital, Accra, colorectal cancer ranks third among the most frequent cancers, and also ranked tenth among cancer death in the country. M utations in the hMLH1 gene are responsible for the bulk of known instances of hereditary non-polyposis colorectal cancer despite the presence of a minor number of variation in the other mismatch repair (MMR) genes(such as hMSH2,hMSH3, hMSH6, hPMS1, and hPMS2). In fact, over 300 germ line mutations have been identified in the MLH1 gene which can be diagnosed easily by automated sequencing. Accordingly, exons 16 and 18 of the MLH1 gene are designated as genetic hotspots for mutations, which agrees with other populations findings. Several studies have also discovered alterations in this gene and exon, and depending on where you live, its presence varies. Aim: Study therefore looked at mutations in exon 16 of the MLH1 gene associated with colorectal cancer in Ghanaian colorectal cancer patients. Methodology: This was a case-control study in which 71 Ghanaian confirmed colorectal cancer patients (cases), who had been clinically and histologically diagnosed by doctors, compared to 68 non-CRC healthy Ghanaians (controls). A questionnaire was used to obtain patients information, and 5mls of whole blood was taken into an EDTA tube. The buffcoat (white blood cells) obtained from the whole blood was used to extract DNA. Primers targeting exon 16 of the MLH1 gene were designed and used to amplify exon 16 from the extracted DNA using polymerase chain reaction (PCR). Amplified DNA (amplicons) were afterwards sequenced and the sequenced products subjected to bioinformatics analysis to look for any genetic alterations. Results: Out of the 71 case samples, 28(39.4%) samples DNA amplification was detected on the agarose gel to the expected band size of 195 bps. All the 68 control samples were amplified to the expected band size of 195 bps. Out of the 139 study samples collected, 96 samples (71 cases, 25 controls) were sequenced. For the case samples; 14(19.7%) out of the 71 case samples were without MLH1 exon 16 region; 30(42.3%) samples had good nucleotide sequence of which 2 had a single guanine (G) nucleotide insertion when aligned with healthy control and reference sequence. Twenty five (25) case samples (35.2%) had sequences that were not clear. For the control samples, all (25) had fairly good nucleotide sequences that had 100% alignment with the reference sequence. Conclusion: This study is the first compiled molecular information on the Ghanaian CRC population. The study reported two types of mutations; whole exon (16) deletion and a single guanine nucleotide insertion (frameshift) mutation at codon 596 of the coding sequence of exon 16 MLH1 protein. Whole exon (16) deletion in this study accounted for 19.7% (14/71) of the total mutations found within the MLH1 exon 16 gene while insertion frameshift mutation was observed in 2.8% (2/71) of the cases.
MPhil.Medical Biochemistry
Keywords: Colorectal cancer (CRC); Sub-Saharan Africa; Colorectal Cancer Patients; Korle- Bu Teaching Hospital